(:unas) unassigned - Christoforou, Maria (My University, 2018)
Represented Agios Ioannis Lyceum in Synaxis International Conference, 1998 for being the student with the highest grades in English and in French. Organized by Lanition Lyceum of Limassol for learners of English and French.